John Candy : a life in comedy - Myers, Paul, 1960- (House of Anansi Press, 2025)
"From his humble beginnings in sketch comedy with the Toronto branch of Second City, to his rise to fame in SCTV and Hollywood film classics like Planes, Trains and Automobiles, The Great Outdoors, and Uncle Buck, John Candy captivated audiences with his self-deprecating humour, emotional warmth, and gift for improvisation. Now, for the first time since Candy's tragic death, bestselling biographer Paul Myers tells the full story of the man behind the laughs. Drawing on extensive research and exclusive interviews with many of Candy's closest friends and colleagues, including Dan Aykroyd, Chevy Chase, Tom Hanks, Ron Howard, Steve Martin, Catherine O'Hara, Martin Short, and many more, John Candy: A Life in Comedy celebrates the comedian's unparalleled talent, infectious charm, and generosity of spirit. Through ups and downs, successes and failures, and struggles with anxiety and self-doubt, Candy faced the world with a big smile and a warm demeanour that earned him the love and adoration of fans around the world"--